The Relationship Between Hospital Service Quality Factors and Outpatient Satisfaction Among Patients with Type II Diabetes Mellitus - Arianti Anaya; I Nyoman Ehrich Lister; Linda Chiuman; Chrimis Novalinda Ginting (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aimed to investigate the relationship between hospital service quality factors and outpatient satisfaction among Type II Diabetes Mellitus patients. The research employed a quantitative cross-sectional approach with a sample of 150 Type II Diabetes Mellitus outpatients selected through systematic random sampling from three public hospitals in Indonesia. Data were collected using validated questionnaires measuring five dimensions of hospital service quality: physical evidence, medical staff reliability, medical staff responsiveness, attention to patients, and comfort. Multiple linear regression analysis was used to examine the relationships between variables. Results revealed significant positive correlations between all service quality factors and outpatient satisfaction (p<0.05), with medical staff reliability (β=0.32) and attention to patients (β=0.28) demonstrating the strongest associations. The findings suggest that enhancing these service quality dimensions, particularly through improved medical staff competence and patient-centered care approaches, could significantly improve satisfaction among Type II Diabetes Mellitus outpatients. This study contributes to the growing body of evidence supporting the importance of service quality in chronic disease management within Indonesian healthcare settings.